Design of Fe and Cu bimetallic integration on N and F co-doped porous carbon material for oxygen reduction reaction. (8th February 2022) - Liu, Siyan; Yang, Huitian; Yao, Lei; Peng, Hongliang; Huang, Pengru; Lin, Xiangcheng; Liu, Lihua; Zhang, Huanzhi; Cai, Ping; Wen, Xin; Zou, Yongjin; Xiang, Cuili; et al.
Abstract: At present, fuel cell is considered to be one of the most ideal application technologies of hydrogen energy. In order to develop fuel cells on a large scale and in a sustainable way, low platinum or non-platinum oxygen reduction catalyst has become a research hotspot. In this work, a kind of doped carbon-based catalyst MPFe1 Cu1 -850 is prepared by high temperature synthesis. The catalyst has an ultra-thin lamellar porous structure. In an acidic medium, the MPFe1 Cu1 -850 displays good oxygen reduction reaction (ORR) activity (ΔE1/2  = 0.725 V). In addition, it shows better stability (91%) and higher methanol tolerance than that of commercial Pt/C catalyst. In our catalyst MPFe1 Cu1 -850, the contents of nitrogen, iron and copper are 10.31 at.%, 0.51 at.%, and 0.50 at.%, respectively. This work shows that high N content, and the proper ratio of iron to copper (Fe:Cu = 1:1), are conducive to the enhancement of ORR activity. Highlights: Design a Fe and Cu bimetallic load on N- and F co-doped carbon material. The N content of the doped carbon catalyst, MPFe1 Cu1, is up 10.31 at.%. When the ratio of Fe: Cu = 1, the ORR activity of the catalyst is enhanced.